Movement of Translocated Adult Sicklefin Redhorse (Moxostoma sp.) in the Oconaluftee River, North Carolina: Implications for Species Restoration - Jessica L Davis; David P Gillette; C. Reed Rossell Jr.; Michael J. LaVoie (Southeastern Fishes Council Proceedings, 2020)
The Sicklefin Redhorse is a rare, undescribed species of Moxostoma, endemic to the Hiwassee and Little Tennessee River basins of western North Carolina and northern Georgia, where it has been eliminated from much of its native range. It is listed as endangered in Georgia and threatened in North Carolina. Although it has not been granted federal protected status, this species is the subject of a Candidate Conservation Agreement between federal, state, tribal, and private stakeholders, of which one objective calls for the re-establishment of Sicklefin Redhorse populations throughout its historical range. The objective of our study was to evaluate suitability of North Carolina’s upper Oconaluftee River for reintroduction of Sicklefin Redhorse, by tracking movement patterns of translocated individuals. Ten native Sicklefin Redhorse were collected from the Tuckasegee River in Swain County, NC, implanted with radio transmitters and translocated into the Oconaluftee River upstream from Ela Dam. Fish were tracked individually using radio telemetry for six months. Movement patterns for newly translocated fish, as well as seasonal patterns for females, were comparable to those shown in previous studies within the current range of Sicklefin Redhorse. Although some fish moved extensively, the sedentary patterns observed in females suggests that the upper Oconaluftee River may provide suitable overwinter habitat for the Sicklefin Redhorse. However, additional data are needed concerning spawning suitability and rates of downstream migration past Ela Dam before reintroducing Sicklefin Redhorse back to this portion of its native range.
Keywords: Sicklefin Redhorse; Moxostoma; Restoration; Impoundment; Habitat Fragmentation